Alteration of the ERK5 pathway by hydroxysafflor yellow A blocks expression of MEF2C in activated hepatic stellate cells in vitro: Potential treatment for hepatic fibrogenesis. (April 2014) - Dong, Haiying; Liu, Yuzhang; Zou, Yu; Li, Chengchong; Li, Libo; Li, Xiaoming; Zhao, Xuemei; Zhou, Li; Liu, Jicheng; Niu, Yingcai
Abstract Context: Hepatic fibrosis ultimately leads to cirrhosis if not treated effectively. Hepatic stellate cells (HSC) are a main mediator of hepatic fibrosis through the accumulation of extracellular matrix proteins. Suppression activation of passaged HSC has been proposed as therapeutic strategies for the treatment and prevention of hepatic fibrosis. Objective: To evaluate the effect of hydroxysafflor yellow A (HSYA), an active chemical compound derived from the flowers of Carthamus tinctorius L. (Compositae), on HSC inhibition, and to begin elucidating underlying mechanisms. Materials and methods: Primary HSCs were isolated from rats by in situ pronase/collagenase perfusion. Culture-activated HSCs were treated with or without HSYA at 30 μM in the presence or absence of PD98059 for 48 h, and then cell proliferation was measured by MTS assays. Messenger RNA (mRNA) expression was quantified by polymerase chain reaction, and protein was quantified by Western blots or enzyme-linked immunosorbent assays. Results: HSYA significantly inhibits culture-activated HSC proliferation in a dose-dependent and time-dependent manner with an IC50 value of 112.79 μM. HSYA (30 μM) induce the suppression of HSC activation, as indicated by decreases in contents of type I alpha collagen in HSC-cultured media and expression of α-smooth muscle actin protein in culture-activated HSC by 55 and 71%, respectively. HSYA (30 μM) also caused significant decreases in mRNA expression of type III alpha collagen in HSC by 28%. HSYA (30 μM) suppresses myocyte enhancer factor 2 C (MEF2C) expression both at its mRNA and protein levels by 60 and 61%, respectively. Further study demonstrated that HSYA (30 μM) caused significant decreases in p-ERK5 by 49%. Blocking extracellular signal-regulated protein kinase 5 (ERK5) activity by XMD 8--92, an ERK5 inhibitor, markedly abrogated the inhibitive effects of HSYA on HSC activation, and blocked the HSYA-mediated MEF2C down-regulation. Conclusions: HSYA suppress HSC activation by ERK5-mediated MEF2C down-regulation and makes it a potential candidate for prevention and treatment of hepatic fibrogenesis.